Contractual Liability and Compensation for Moral Harm - Dacoronia, Eugenia (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
In Greece, the breach of contractual obligation is in principle disapproved by law, it creates, however, only an obligation for the payment of compensation and not an additional obligation for the restoration of moral harm, because the sole non-performance of the contractual obligations cannot cause moral harm. Consequently, according to the Greek legislator, a possibility for the existence of a relevant pecuniary compensation does not exist. Pecuniary compensation for non-pecuniary damage is exceptionally recognized and only in cases defined by law (Art. 299 GCC). For example, it is recognized in the cases of infringement of the personality (Arts. 57, 59 GCC) and of tort, especially for the person who suffered an attack upon his health, honour, or chastity or who was deprived of his liberty (Art. 932 GCC). In case, however, the violation of the contractual obligation constitutes at the same time - and independently from the existence of the contract - a tort, then it is settled case law in Greece that there is concurrence of contractual and delictual obligation. In that case, the provisions of tort (art. 914 ff. GCC) may apply, in which case, provided that moral harm is sustained, compensation for such moral harm may be sought. Deciding, however, whether the violation of the contractual obligation constitutes at the same time - and independently from the existence of the contract - a tort is not always easy. The tendency noted in the international texts aiming at the unification of law in Europe is the restoration of moral harm also in cases of breach of a contract. For example, art. 9:501 of the Principles of European Contract Law, PECL and art. 7.4.2 of the Unidroit Principles provide for the possibility of the contracting party to request the restoration of non-pecuniary damage in cases of unjustifiable breach of a contract. Thus, the override of the prohibition set in art. 299 GCC attempted by the Greek doctrine and jurisprudence through the provisions about personality protection and the application of art. 932 GCC, where there is concurrence of contractual and delictual liability, is justified and confirms that art. 299 GCC was rightly criticized almost unanimously by the Greek doctrine already since its introduction as against the tradition of Greek Law and due to the non-lenient situations it causes.